Creating and Testing a Sensory Well–Being Hub for Adolescents with Developmental Disabilities. Issue 1 (March 2020) - Park, Giyoung; Nanda, Upali; Adams, Lisa; Essary, Jonathan; Hoelting, Melissa
While multisensory environments (or sensory rooms) are gaining traction in the learning environments, few studies have assessed the comparative effectiveness of specific elements and the link to individuals' unique sensory needs. This study describes the creation and evaluation of a sensory well–being hub for diverse learners with developmental disabilities and distinct sensory profiles in a Chicago public high school. The sensory well–being hub is a simple and adaptable freestanding structure with various sensory affordances, supporting a wide range of atypical sensory processing in neurodiverse individuals. Data were collected during one academic year using surveys, focus groups, field observations, sensor data, log–in sheets, and student records. Results show that the hub was used for both scheduled (preventive) visits and unscheduled (spontaneously needed) ones. The most visited elements in the hub were a beanbag with weighted blanket, sensory cocoon with tensile fabric and a media wall, and a fidget wall with various components. The sensory affordances most often sought by users were compression, quietness, tactility, and proprioception. Students with autism spectrum disorders (ASD) differed from those without ASD in the ways they used sensory intervention even though the two groups were equivalent in sensory profiles (in thresholds for registration and active–to–passive response to stimuli). Based on the study findings, design suggestions were included to inform sensory hub design in other learning environments.